How efficient could photocatalytic CO2 reduction with H2O into solar fuels be?. (15th October 2020) - Zhu, Zhonghui; Liu, Xianglei; Bao, Chuang; Zhang, Kai; Song, Chao; Xuan, Yimin
Highlights: An efficiency evaluation model of water-based photocatalytic CO2 reduction system was established. Regulation of recombination coefficient and gas coverage ratio can enhance efficiency. Efficiency limit of photocatalytic reduction of CO2 with H2 O into CH3 OH is 46.7%. Efficiency limit for photocatalysis system combined with up-conversion materials is 59%. Abstract: Photocatalytic carbon dioxide (CO2 ) reduction in aqueous media provides a potential and convenient way for fulfilling increasing fossil energy demand and relieving global warming problems. However, the efficiency limit for the photocatalytic CO2 reduction system still remains unclear. Here a comprehensive model of the photocatalytic CO2 reduction system is established to theoretically evaluate the efficiency limit, in which the light absorption, charge carrier recombination behaviors, and surface reaction processes are considered. Effects of Auger coefficient and the gas coverage ratio on the energy conversion efficiency are discussed to provide feasible enhancement approaches. Experimental efficiencies are compared with theoretical results to analyze the origin of low efficiencies. The photocatalytic reduction of CO2 into methanol is taken as an example, the energy conversion efficiency limit amounts to be 46.7%. To further improve the utilization of solar spectrum, up-conversion materials are incorporated into the photocatalytic system. The maximum efficiency of photocatalytic reduction of CO2 to methanol is predicted to be 59%. This paper unveils the upper efficiency limit of photocatalytic reduction of CO2 and provides the guidance for design of efficient photocatalysts and systems.